Milling Machine and Cleaning Egg Cleaning Reballs Automatically Completed With the Screw Conveyor System and Auto Washer - Fajar Septiawan Dwi Angoro; Aisyah Nur Khalifah; Syahrul Gunawan; Dandy Syah Putra; Fakhriyah Qothrun Nada; Wahyu Dwi Kurniawan (Journal of World Conference (JWC), 2020)
Milling Machine And Cleaning Egg Cleaning Reballs Automatically Completed With The Screw Conveyor System And Auto Washer is made with the aim of increasing productivity and the effectiveness of the production of SME quail egg satay in Surabaya. Egg peeler This semi automatic quail is designed as simply as possible to make it easier mass production and easy maintenance. This machine is added screw conveyor system which is covered with sponge and machine walls, there is a polisher made from stainless which serves as a boiled egg quail peeler. The addition of an auto water washer on this machine uses a hose connected with a water tap to be able to clean automatically when the engine have started working on peeling boiled eggs. Material in direct contact with eggs using stainless steel type 430 SS foodgrade with 3mm thick to maintain the level of hygiene of the production process. Then the system the drive on this machine uses a DC electric motor with a power of ½ PK which transmitted by pulleys and V-belts to reduce input power to more smooth round. Selection of the ½ PK motor is intended for rotation in this engine can be smoother and softer, not too fast so the egg doesn't break. Dimension machine made measuring 110 cm x 65 cm x 52 cm with stripping capacity 1200 quail eggs / hour. Features that have this machine can improve the productivity process of SME quail eggs is threefold, so that the problem of SMEs is quail egg satay for stripping and cleaning the eggs takes a long time to complete.